Key factors influencing CO2 emissions in the southern power grid of China - Huang, Yanlu; Wang, Zifei; Zhang, Fan; Tan, Junfeng; Hu, Xudong (Frontiers in Environmental Science, 2025)
The power sector is the largest contributor to global carbon emissions, particularly in China, where decarbonizing electricity generation is crucial for achieving carbon neutrality. Understanding the drivers of carbon emissions in this sector is vital for formulating effective policy measures. This study investigates carbon emissions from the Southern Power Grid of China between 2013 and 2021. It employs decomposition analysis techniques to identify the key driving factors across five provinces within the grid region. GDP per capita emerged as a major driver of electricity-related carbon emissions across provinces. Guangdong, Guangxi, and Hainan achieved reductions in per capita emissions from electricity supply, while Guizhou and Yunnan showed improvements through different mechanisms. The analysis revealed substantial provincial disparities in emission patterns, closely associated with differences in economic output and electricity generation structures. Contribution rate analysis further highlighted varied progress toward carbon peaking and heterogeneous supply methods. These findings underscore the importance of recognizing interprovincial differences in emission drivers within the Southern Power Grid. Tailored, region-specific policy interventions are essential to accelerate the sectoral transition toward carbon neutrality and to ensure balanced progress across provinces.